La réduction de la valence verbale : le cas de la passivation en amazighe - Lhassane Andam (Multilinguales)
The purpose of this article is to describe the passive construction as a reducing form of verb valence in amazighe. Thus, we will be allowed to feature the various changes that affect the structure periphrastically, from the active diathesis to the passive diathesis. Our analysis reveals, on the one hand, with a transformational view the paradox of roles and functions that characterizes the passive form. On the other hand, we will introduce an alternative approach where the passive form is considered as a process involving the reversal of perspective, an approach which uses positioning rules that involve no transformational operation.